3.  Verify that – (– x) = x for 

      (i) x = \frac{11}{15}          (ii) x = \frac{-13}{17}

Answers (1)
D Divya Prakash Singh

(i)  We have  x = \frac{11}{15}

     The additive inverse of x = \frac{11}{15}  is -x = \frac{-11}{15}

     The same equality  \frac{11}{15}+\left ( \frac{-11}{15} \right ) = 0 

     which  implies  -\left ( \frac{-11}{15} \right ) = \frac{11}{15}      shows that  -(-x) = x

(ii) Additive inverse of x = \frac{-13}{17} is -x = \frac{13}{17}                        (since \frac{-13}{17}+\frac{13}{17} = 0)

     The same quality shows that the additive inverse of \frac{13}{17} is \frac{-13}{17}

     i.e., -(-x) = x

Exams
Articles
Questions